Peningkatan Kreativitas dan Keterampilan Proses Sains Siswa melalui Penerapan Model Group Investigation - Delismar Delismar; Rayandra Asyhar; Bambang Hariyadi (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2013)
Learning process in SMPN 5 Jambi is still dominated by the behavior paradigm with low learning outcomes.This study aims to reveal the significance of the student-centered learning, using quasi-experimental design. Weemployed research instrument of science process skills test results and creativity questionnaire. The collecteddata were analyzed using ANOVA and Tuckey test. The results, there was no significant of the effect of theinvestigation group model and creativity on science process skills (p = 0.083). The results also indicate theinteraction between group investigation model and science process skills (p = 0.03). The teacher applies thegroup investigation model for high creativity students.